2017
DOI: 10.1111/jocd.12456
|View full text |Cite
|
Sign up to set email alerts
|

Serum homocysteine levels in acne patients

Abstract: Hyperhomocysteinemia may be an independent risk factor for acne vulgaris. Detection of serum HCY is important for acne patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 12 publications
(10 reference statements)
0
9
0
2
Order By: Relevance
“…Elevation in serum vitamin B 12 in acne patients due to the correlation between the severity of acne and vitamin B 12 that proved in this study. Also result showed a slight increase in serum homocysteine in patients, but there was no significant difference observed as compared with control group and these results disagree with Jiang et al that showed significantly elevated serum homocysteine levels in patients with severe and moderate acne compared with the control group [9]. However, it can be reported that different vitamin supplements (the most prominently are vitamin B 12 ), could exacerbate existing acne and/or lead to the development of acneiform eruptions [10] .…”
Section: Discussionmentioning
confidence: 84%
“…Elevation in serum vitamin B 12 in acne patients due to the correlation between the severity of acne and vitamin B 12 that proved in this study. Also result showed a slight increase in serum homocysteine in patients, but there was no significant difference observed as compared with control group and these results disagree with Jiang et al that showed significantly elevated serum homocysteine levels in patients with severe and moderate acne compared with the control group [9]. However, it can be reported that different vitamin supplements (the most prominently are vitamin B 12 ), could exacerbate existing acne and/or lead to the development of acneiform eruptions [10] .…”
Section: Discussionmentioning
confidence: 84%
“…The results of our meta‐analysis show that acne patients on Iso therapy exhibited higher levels of plasma Hcy and lower levels of plasma folic acid and vitamin B12 compared with premedication levels. Given that acne itself might increase plasma Hcy levels relative to unaffected healthy controls, we can assume that the risk of HHcy would be increased even more in acne patients on Iso therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidence has shown acne to be a multifactorial chronic systemic condition and a possible early sign of underlying systemic diseases . Several studies have reported elevated levels of homocysteine (Hcy) in combination with lower levels of folate in the plasma of acne patients . Hcy is a sulfur‐containing amino acid formed from methionine.…”
Section: Introductionmentioning
confidence: 99%
“…Современный образ жизни и питания предрасполагает к тому, что дефицит фолатов может быть достаточно распространен даже у женщин в экономически развитых странах [39][40][41]. Эта проблема тем более важна, что латентный дефицит фолатов можно выявить только при углубленном обследовании.…”
Section: To Cite This Articleunclassified